Trialled IndoDairy Focus Farms as An Extension Approach for Smallholder Dairy Farmers in West Java Province, Indonesia - Hanifah, Vyta W; Syahnurotin, Attin; Ritchie, Zita; Granzin, Brad (Agro Ekonomi, 2025)
This paper details how the IndoDairy Project fostered a sense of community and shared learning by trialling a Focus Farm as a new extension approach. The selection process was collaborative, with two farmers successfully passing the rigorous processes. These processes included an interview on their motivation, verification through a farm visit, assessment by comparing the strengths and weaknesses among all candidates, and confirmation on the agreement as a chosen focus farmer. The chosen farmers also had the opportunity to select their own Support Farmers group, which comprised around 3-5 people. The Project Team, a key facilitator in the trial, recommended experts as the Advisory Group, who were selected adjustably based on their expertise to support the implementation of technology interventions. In total, there were ten farmers and seven advisors involved. The Focus Farm had six monthly meetings to monitor and update the farm condition and then discuss what works well and what needs improvement. The project facilitated farmers to trial planting high-quality forages and making silage from these forages. Moreover, the Project also facilitated laboratory analyses for samples of soil, forages, concentrates, and composts they used when planting the forages. Looking at the laboratory results, farmers learned about nutrition balance from local feed resources. Lastly, Open Day aimed to share experiences and lessons learned about being a Focus Farm with more farmers and stakeholders, such as farmer-to-farmer learning.